The efficacy and safety of pioglitazone in psoriasis vulgaris: A meta-analysis of randomized controlled trials. Issue 32 (7th August 2020) - Chen, Pengfei; Chen, Xiubing; Lei, Lei; Zhang, Yang; Xiang, Jianjun; Zhou, Jinxia; Lv, Jun
Abstract : Abstract: Pioglitazone may have potential benefits in the treatment of cutaneous and metabolic derangements of psoriasis, but its role in the treatment of psoriasis remains in debate. We therefore conducted a meta-analysis to evaluate the clinical efficacy and safety of pioglitazone in psoriasis vulgaris (PsV). We performed a comprehensive search in database of PubMed, Web of Science, Cochrane library, Embase and China National Knowledge Infrastructure (CNKI), and Wan fang database through March 2019 to identify eligible studies. Randomized controlled trials that have evaluated the effect and safety of pioglitazone in PsV were included. Treatment success was defined as ≥75% reduction in psoriasis area and severity index (PASI) score after treatment. Weighted mean differences (WMD), relative risks (RRs) and the corresponding 95% confidence intervals (CIs) were pooled to compare the clinical efficacy and safety between different groups. Six randomized controlled trials (n = 270) were included. Meta-analysis showed that pioglitazone was associated with a remarkable reduction in PASI score in patients with PsV (weight mean difference: 2.68, 95% CI 1.41–3.94, P  < .001). The treatment success rate in the pioglitazone group was higher than in the control group (RR 3.60, 95 CI 1.61–8.01, P  < .001). Compared with control group, pioglitazone was not related to a pronounced increase in total adverse events (RR 1.180, 95 CI 0.85–1.63, P  = .33). Moreover, the risk of common adverse events in the 2 groups were similar, such as elevated liver enzyme, fatigue, nausea, weight gain. This meta-analysis suggested pioglitazone is an effective and safe drug in the treatment of patients with PsV. Abstract : Supplemental Digital Content is available in the text